Community Consumption of Traditional Medicine and Health Supplements During the Coronavirus Disease-2019 Pandemic - Hilyatul Fadliyah; Atik Nurwahyuni; Faradiba Faradiba (Journal of Consumer Sciences, 2021)
Coronavirus disease-2019 (COVID-19) encourages the community to prioritize basic and personal health needs. This study aimed to explore the consumer behaviour of traditional medicine and health supplements during the COVID-19 pandemic in Indonesia using the Consumer Decision Model approach. A quick online cross-sectional survey involving 215 respondents was carried out from December 23, 2020, until January 2, 2021. This study revealed that the majority of respondents consume the products as forced by the pandemic situation, and their use has increased than before the pandemic. The primary reason for consuming the product is to increase their immunity during a pandemic, and they felt more healthy after consuming it. Social media and television are the primary sources of product information. Furthermore, we found that the majority of respondents were branded product consumers. Respondents were more likely to have good behaviour based on knowledge of the products' legality, dosage, indication, instructions for use, and expiration date. This study sets appropriate consumer behaviour and performs the statistical tests only for branded product consumers. It is concluded that consumer behaviour in this study is related to product advertisement exposure and acceptance, environmental influence, and individual difference.